Երեմիա Չելեպի Քյոմուրճյանի «Օրագրութիւն», «Տարեգրական պատմութիւն» երկերը և Միքայել Չամչյանի «Պատմութիւն հայոց» աշխատությունը (բնագրագիտական քննություն) - Այվազյան, Գայանե (ՀՀ ԳԱԱ հրատ.)
Взаимосвязи исторического наследия известного историографа 17-ого века Еремии Челеби Кемурчяна многогранны и разнообразны. Статья посвящена вопросу источниковедческих связей между двумя основными работами Еремии Кемурчяна - “Дневником” и “Летописной историей” и “Историей Армении” Микаэла Чамчяна. Interrelation of historiographical heritage of the XVIIth century eminent historiographer Jeremia Chelebi Qyomurtchyan is multifaceted and diversified. This article focuses on the issue of source study interrelations between two valuable works of Jeremia Qyomurtchyan: “Diary” and “Annalistic history” and “History of Armenia” by Mikayel Chamchian.
Keywords: Հայագիտություն; Պատմություն